Growing brands through sponsorship : an empirical investigation of brand image transfer in a sponsorship alliance - Gross, Philip (Strategie, Marketing und Informationsmanagement, 2015)
Philip Gross addresses a new opportunity for growing brands that may reside within a sponsorship alliance. Typically, brands vie for image transfer from an event or other property when entering a sponsorship engagement. Yet this practice leaves a valuable part of a sponsorship alliance unexploited. Specifically, the author infers from theories of social and cognitive psychology to propose and test a research model that accounts for a sponsor to also gain from brand attitude and personality traits innately tied to a co‑sponsor of the same event. The results provide evidence for direct image transfer between two sponsor brands. Hence, pairing with a co‑sponsor might fortify or dilute a sponsor brand's image depending on the expediency of the image conveyed by that ally.     Contents ·        Brands and Identity-Based Brand Management ·        Sponsorship Alliance ·        Brand Image Transfer: Attitude and Personality    Target Groups ·        Researchers and students in the fields of marketing, brand management and brand image transfer ·        Practitioners in the field of sponsorship management    The Author Dr. Philip Gross obtained his doctoral degree from the Institute of Marketing and Management at the University of Hanover where he works with Prof. Dr. Klaus-Peter Wiedmann. As a founding partner and academic advisor to "Axonalliance - Bright Strategies" he engages with clients on issues of brand leadership and strategic marketing.  .